A REPRESENTATION OF MALE HOMOSEXUAL CHARACTERSIN A NOVEL ENTITLED "LELAKI TERINDAH" - Irna Carnawianty, - (2008)
The research paper is entitled A Representation Of Male Homosexual Characters in the novel entitled Lelaki Terindah written by Andrei Aksana. It aimed at finding out the representation of a male homosexual characters in the novel. Qualitative descriptive method was applied in this research. Queer theory proposed by Butler (1990) is used as the theoretical framework of the research. The text indicated that presentation of male homosexual characters is divided into two: feminine male homosexual character and masculine male homosexual character. In the view of queer theory, the representation of male homosexual character conforms to Butler's theory (1990) who believes that gender is performative and socially constructed.